Does Pain in Individuals with Multiple Sclerosis Affect Employment? A Systematic Review and Meta-Analysis. (2013) - Shahrbanian, Shahnaz; Auais, Mohammad; Duquette, Pierre; Anderson, Katie; Mayo, Nancy E
Abstract : BACKGROUND: Individuals with multiple sclerosis (MS) experience some of the highest unemployment rates among all groups of chronic illnesses. Pain has been found to be a common reason for sick leave or early retirement in healthy populations or other groups with chronic illness; however, there is little awareness regarding the effect of pain on the work status of individuals with MS. OBJECTIVES: To estimate the extent to which individuals with pain differ in employment status compared with those without pain among MS patients. METHODS: An extensive systematic review of the scientific literature was performed within the framework of the Cochrane Collaboration to identify studies focusing on the effect of pain on employment in individuals with MS. The following databases were searched: PubMed, EMBASE, PsychInfo, Web of Science, MD Consult and Elsevier, and Science Direct. The methodological quality of studies was assessed using the McMaster Critical Review Form. RESULTS: Ten articles met the inclusion criteria and were included in the systematic review. Of these studies, five that exhibited clinical, methodological and statistical homogeneity were included in the meta-analysis. The between-groups (pain + versus pain −) pooled random OR of being employed was 0.7 (strong), and was significantly different from unity (95% CI 0.5 to 0.9; P=0.001). CONCLUSIONS: The results of the present study indicated that individuals with MS who experience pain were significantly more likely to report a decreased employment rate than individuals with MS who were pain free. Erratum to "Does Pain in Individuals with Multiple Sclerosis Affect Employment? A Systematic Review and Meta-Analysis" dx.doi.org/10.1155/2013/620869